2017
DOI: 10.1016/j.sleep.2017.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea in pregnancy is associated with adverse maternal outcomes: a national cohort

Abstract: Objective Pregnancy and the obesity epidemic impacting women of reproductive age appear to predispose women to obstructive sleep apnea (OSA) in pregnancy. The aim of this study is to examine the association between OSA and adverse maternal outcomes in a national cohort. Methods The National Perinatal Information Center in the US was used to identify women with a delivery discharge diagnosis of OSA from 2010 to 2014. We used the International Classification of Diseases, 9th Revision to classify OSA diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
121
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 36 publications
(53 reference statements)
3
121
1
Order By: Relevance
“…[27,29,30] SDB is associated with a plethora of negative maternal, obstetric and perinatal outcomes including cardiovascular and metabolic disease, fetal growth restriction, preterm birth, low birth weight, operative delivery, low 5-minute Apgar score, stillbirth and perinatal death, longer hospital stay, as well as maternal and neonatal admission to intensive care. [8,9] More recent evidence also suggests that offspring of women with high levels of daytime sleepiness have poorer executive function and increased neuropsychiatric problems in early childhood.…”
Section: Sleep Disordered Breathing In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…[27,29,30] SDB is associated with a plethora of negative maternal, obstetric and perinatal outcomes including cardiovascular and metabolic disease, fetal growth restriction, preterm birth, low birth weight, operative delivery, low 5-minute Apgar score, stillbirth and perinatal death, longer hospital stay, as well as maternal and neonatal admission to intensive care. [8,9] More recent evidence also suggests that offspring of women with high levels of daytime sleepiness have poorer executive function and increased neuropsychiatric problems in early childhood.…”
Section: Sleep Disordered Breathing In Pregnancymentioning
confidence: 99%
“…[1,4] Perturbations in sleep are common in pregnancy, with women often describing increased frequency of awakenings, lower overall sleep duration and higher levels of daytime sleepiness compared with pre-pregnancy patterns. Indeed there is mounting evidence showing that sleep abnormalities negatively impact obstetric and perinatal outcomes [5][6][7][8][9][10][11] and treatment, particularly those related to obstructive airway symptoms, ameliorates some of these complications. [12][13][14] Maternal sleep position has also been linked with adverse outcomes particularly stillbirth.…”
Section: Introductionmentioning
confidence: 99%
“…; Bourjeily et al . ). It has been suggested that the incidence of OSA in pregnancy is dramatically under‐reported (Pien et al .…”
Section: Introductionmentioning
confidence: 97%
“…), and in industrialised countries OSA during pregnancy is increasing due to the obesity epidemic, particularly in younger women, and is associated with a number of pregnancy complications (Bourjeily et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…The degree of OSA appears to be linearly related to cardiovascular risk. [8] Accumulating evidence suggests this relationship may also exist in pregnancy with several studies reporting an association between SDB and gestational hypertensive disorders, [3,9,10] although obesity can act as a confounder to this relationship. [11] Hypertensive disorders of pregnancy (HDP), particularly preeclampsia, are associated with placental dysfunction resulting in impaired fetal growth and increased risks of acute compromise.…”
Section: Introductionmentioning
confidence: 99%